Tanggung Jawab Misioner Guru Kristen Dalam Dunia Pendidikan - Kana Kana; Leniwan Darmawati Gea; Sri Ernawati; Wike Mary Agmy (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2022)
Education is an important part of the Christian mission because the Lord Jesus himself emphasized it in the Great Commission as a command that must be carried out. This task is for all Christians who are responsible for transmitting God's truth from generation to generation through teaching. The aim of this research is to focus on Christian teachers as a profession and part of all God's people, who are allowed to be preachers and teachers of God's truth to sinners. The hope is that Christian teachers will not only act as professional workers, but more than that they must carry out their missionary duties as a manifestation of God's call to them. The research method used is the library method. The results of this research are that teachers are a noble task because they carry out the main responsibility of the church, namely education as part of the mission. In this regard, the status as a Christian teacher is God's call which confirms his missionary function and responsibility, namely bringing students or students to the knowledge of the Lord Jesus Christ.